Centers and isochronicity of some polynomial differential systems - Fernandes, Wilker Thiago Resende (2017)
The center-focus and isochronicity problems are two classic problem in the qualitative theory of ordinary differential equations (ODEs). Although such problems have been studied during more than hundred years a complete understanding of them is far from be reached. Recently the computational algebra tools have been contributing significantly with the development of such problems. The aim of this thesis is to contribute with the studies of the center-focus and isochronicity problem. Using computational algebra tools we find conditions for the existence of two simultaneous centers for a family of quintic systems possessing symmetry. The studies of the simultaneous existence of two centers in differential systems is known as the bi-center problem. We investigate conditions for the isochronicity of centers for families of cubic and quintic systems and we study its global behaviour in the Poincaré disk. Finally, we study the existence of invariant surfaces and first integrals in a family of 3-dimensional systems. Such family is known as the May-Leonard asymmetric system and it appears in modelling, for instance it is a model for the competition of three species.